In vitro 50 Hz magnetic field long-term exposure: Cytogenetic tests on human lymphoblastoid TK6 cells and validation of the test environment - Nguyen, Ha; Ledent, Maryse; Beauvois, Véronique; Anthonissen, Roel; Verschaeve, Luc; Collard, Jean-Francois; Hinsenkamp, Maurice; Feipel, Veronique; Mertens, Birgit (MethodsX, 2020)
Potential health effects of extremely low-frequency (electro)magnetic fields (ELF-(E)MFs) have long been investigated, but the results are still inconclusive. With respect to genotoxicity, sound data related to the effects of long-term exposure to ELF-(E)MFs on the genetic material and the impact of long-term pre-exposure to ELF-(E)MFs on the sensitivity of cells to the damage induced by known mutagens are needed. In this manuscript, an optimized protocol for a combined in vitro comet/micronucleus study to investigate these effects in a human lymphoblastoid cell line (TK6) is provided including the description of a well-validated exposure system. Furthermore, the use of a shielding system to limit background ELF-MFs inside the incubator is described as well.•Optimized protocols for cytogenetic tests with ELF-MFs on TK6 cells ensure the reproducibility of test results.•Validation of exposure environment and exposure system are needed prior to performing tests with ELF-MFs.•A simple, but effective method to shield cells and reduce unintentional ELF-MF exposure consists of using the mu-metal cylinder. This is of particular interest when studying the effects of low exposure levels. [Display omitted]